The role of oestrogenes in carcinogenesis - Piekutowski, Krzysztof; Roszkowski, Krzysztof; Foksiński, Marek; Oliński, Ryszard (Contemporary Oncology/Współczesna Onkologia, 2002)
Both oestrogens and their metabolites are believed to be etiological factors in breast, uterine and ovarian carcinomas. Those hormones stimulate the proliferation of cells, which proceeded by DNA replication, offers the opportunity of fixing potentially carcinogenic mutations, both spontaneous and those caused by a number of external environmental agents. Four- or fivefold increase of incidence of this carcinoma correlates with the period of employed substitution hormonotherapy. The direct influence of oestrogens on target cells results from combining the steroid - receptor complex with DNA in the cell nucleus. This is the way they regulate the expression of genes and may result in transformation of protooncogens into oncogens. Metabolism of oestrogenes gives rise to a number of metabolites (2-hydroxyoestrones (2-HE), 4-hydroxyoestrones (4HE) 16 a-hydroxyoestrones (16 a-HE), which converted into semiquinones and quinines generate reactive oxygen species (ROS) and directly impair DNA. A frequent effect of the interaction of oestrogen derivatives with DNA is a generator apurinic sites in DNA that result from labilization of N-glycoside bonds. ROS maybe generated during catabolism of oestrogens catalyzed by cytochrome P450 reductase and other electrons-transporting enzymes. This increased production of ROS may result in oxidative stress. The interaction of ROS, especially highly reactive hydroxyl radical with cell components may damage DNA, which in turn may cause the cancer development. The most important of those DNA lesions are modifications of nucleobases, some of which may be responsible for neoplastic transformations. Practically all oestrogen metabolites may be substrates of such reactions. ROS are produced in redox cycles of oestrogens by microsomal, mitochondrial and nuclear enzymatic systems as well as non-enzymatically in reactions with copper (Cu+) and iron (Fe 2+) ions. A production of ROS in the process of oestrogen catabolism may also trigger lipid peroxidation. Products of lipid peroxidation (e.g. malondialdehyde) may react with DNA and produce potentially mutagenic DNA-aldehyde adducts and/or DNA strand brakes. Thus, a generation of oxygen free radicals and different DNA adducts may cause structural changes of the chromosomes that are observed after exposure of the cells to oestrogens. Also the changes in the number of chromosomes are thought to be inducted by catechol metabolites of oestrogens or by oxygen free radicals formed during their metabolism. Although genotoxicity of oestrogens has not been confirmed by bacteriological tests, they are considered to be agents that contribute to cancer promotion and progression.